2006
DOI: 10.1128/cvi.00254-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Immunodominant 18-Kilodalton Small Heat Shock Protein as a Serological Marker for Exposure to Mycobacterium ulcerans

Abstract: While it is well established that proximity to wetlands is a risk factor for contracting Buruli ulcer, it is not clear what proportion of a population living in an area where the etiologic agent, Mycobacterium ulcerans, is endemic is actually exposed to this disease. Immunological cross-reactivity among mycobacterial species complicates the development of a specific serological test. Among immunodominant proteins recognized by a panel of anti-M. ulcerans monoclonal antibodies, the M. ulcerans homologue of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 38 publications
2
82
1
Order By: Relevance
“…Surprisingly, histological approaches showed that the bacilli present in healed tissues are not surrounded by a granuloma-like structure, unlike in the context of latent tuberculosis (42,43). Moreover, this model supports the concept that interindividual variability in the host response to infection by M. ulcerans could be accounted for, at least in part, by host genetic factors (44)(45)(46).…”
Section: Major Data Model Descriptionsupporting
confidence: 65%
“…Surprisingly, histological approaches showed that the bacilli present in healed tissues are not surrounded by a granuloma-like structure, unlike in the context of latent tuberculosis (42,43). Moreover, this model supports the concept that interindividual variability in the host response to infection by M. ulcerans could be accounted for, at least in part, by host genetic factors (44)(45)(46).…”
Section: Major Data Model Descriptionsupporting
confidence: 65%
“…The strains used for this investigation and their origins are as follows: M. ulcerans Agy99, Malaysia 1615, and Japan 753 (21); Ghana IFIK1066089, Ghana Nm50/ 04, Ghana Nm51/04, Ghana Nm53/04, Ghana Nm74/02, Ghana Nm97/02, Ghana Nm98/02, Ghana Nm103/02, and Mexico IFIK 973880 (this study); Ghana Nm18/ 02, Ghana Nm21/02, Ghana Nm31/04, Ghana Nm38/02, and Ghana Nm59/02 (10) (5). Mycobacteria were obtained from cultures as described earlier (19,31), resuspended in phosphate-buffered saline (PBS; pH 7.4), and heat inactivated at 95°C for 60 min.…”
Section: Methodsmentioning
confidence: 63%
“…The observations that active BU occurs in a small proportion of exposed individuals (14,58) and when it develops frequently heals spontaneously (69) suggest the existence of protective immunity. Although the protective mechanisms remain largely unknown, several studies support that adaptive cell-mediated immunity (CMI) is relevant for the control of M. ulcerans (reviewed in reference 53).…”
mentioning
confidence: 99%